Outsourcing via Service Competition - Benjaafar, Saif; Elahi, Ehsan; Donohue, Karen L. (Management Science, 2007)
We consider a single buyer who wishes to outsource a fixed demand for a manufactured good or service at a fixed price to a set of potential suppliers. We examine the value of competition as a mechanism for the buyer to elicit service quality from the suppliers. We compare two approaches the buyer could use to orchestrate this competition: (1) a supplier-allocation (SA) approach, which allocates a proportion of demand to each supplier with the proportion allocated to a supplier increasing in the quality of service the supplier promises to offer, and (2) a supplier-selection (SS) approach, which allocates all demand to one supplier with the probability that a particular supplier is selected increasing in the quality of service to which the supplier commits. In both cases, suppliers incur a cost whenever they receive a positive portion of demand, with this cost increasing in the quality of service they offer and the demand they receive. The analysis reveals that (a) a buyer could indeed orchestrate a competition among potential suppliers to promote service quality, (b) under identical allocation functions, the existence of a demand-independent service cost gives a distinct advantage to SS-type competitions, in terms of higher service quality for the buyer and higher expected profit for the supplier, (c) the relative advantage of SS versus SA depends on the magnitude of demand-independent versus demand-dependent service costs, (d) in the presence of a demand-independent service cost, a buyer should limit the number of competing suppliers under SA competition but impose no such limits under SS competition, and (e) a buyer can induce suppliers to provide higher service levels by selecting an appropriate allocation function. We illustrate the impact of these results through three example applications.